Konsep Mukmin Dalam Al-Quran - Hasanuddin (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2015)
Believers’ sentences in the Koran have a great deal of meaning in both deflation and context. This paper examines the words of ‘Mukmin’ within the Qur’an to form unification of the whole concept from various meanings spreads in the Koran. The author besides using the textual and contextual approach, also uses the maudhu’i (thematic) method to unify all the concepts, thus giving birth to several criteria which can include the understanding of a Mukmin (believer). The criteria included among others: prostration and glorification when warned with the verses of Allah and not being arrogant; accept the verse of Allah and do what is commanded in it; obey and make the apostle a judge; istiqamah (steadfast) in obedience, maintaining dignity, being humble and remembering God frequently.